2002
DOI: 10.1046/j.1472-765x.2002.01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a dextran-binding domain of the dextranase of Streptococcus mutans

Abstract: Aims: To examine the dextran‐binding domain of the dextranase (Dex) of Streptococcus mutans. 
Methods and Results: Deletion mutants of the Dex gene of Strep. mutans were prepared by polymerase chain reaction and expressed in Escherichia coli cells. Binding of the truncated Dexs to dextran was measured with a Sephadex G‐150 gel. Although the Dexs which lacked the N‐terminal variable region lost enzyme activity, they still retained dextran‐binding ability. In addition, further deletion into the conserved region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
3
12
1
Order By: Relevance
“…The deletion of cVR and membrane-anchoring domain seems to have no influence on the dextranase activity on BD-SDS-PAGE-gels. This finding also agreed with a report on the dextranase of S. mutans (25). Comparing the deduced amino acid sequence of dextranases of oral streptococci, an amino acid, tryptophan, is conserved in regions 1, 4, 5, 8, and 9, defined by Aoki and Sakano (1).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The deletion of cVR and membrane-anchoring domain seems to have no influence on the dextranase activity on BD-SDS-PAGE-gels. This finding also agreed with a report on the dextranase of S. mutans (25). Comparing the deduced amino acid sequence of dextranases of oral streptococci, an amino acid, tryptophan, is conserved in regions 1, 4, 5, 8, and 9, defined by Aoki and Sakano (1).…”
Section: Discussionsupporting
confidence: 91%
“…A similar finding has been made in the GH 49 family of dextranases (3). In contrast, the conserved region comprising the catalytic site and dextran-binding domain is responsible for dextranase activity (14,25). In our study, the replacement of Asp-453 with a Glu residue extinguished the activity of dextranase (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…This structural organization is quite similar to the dextranases from S. mutans, S. sobrinus, and S. downei (79). Asp385 of the Dex of S. mutans Ingbritt is essential for enzyme activity, and the catalytic and substratebinding sites are located at different sites within the Dex molecule (78,137). Replacement of Asp385 of DexA from S. mutans Ingbritt results in complete disappearance of enzymatic activity, while the enzyme retains its ability to bind dextran (78).…”
Section: Secondary and Tertiary Structures Of Dextranasesmentioning
confidence: 67%
“…An SDS-PAGE analysis of the recombinant enzyme indicated that there are multiple active dextranase forms (77). Comparison of the amino acid sequences of the Dex proteins and glucosyltransferases indicated that the amino acid sequences of the Dex enzymes produced by S. mutans, S. sobrinus, S. salivarius, and S. downei were similar to those of the catalytic sites of glucosyltransferases of mutans streptococci (78,137).…”
Section: Sequence Comparison Studiesmentioning
confidence: 95%
“…This gene is one of the socalled virulence factors of the pathogen. It codes for an enzyme which cleaves a-1,6-linkages of glucans and is thought to be responsible both for the control of the amount and content of extracellular glucans and for the metabolic utilization of extracellular glucans ( [31] and references therein). The primers used to carry out the PCR process were L-344 (forward primer) and R-467 (reverse primer) [27].…”
Section: Materials and Methods (A) Study Species And Samplingmentioning
confidence: 99%